Determination of Mineral Concentration and Cell-Wall Energy Content of Some Alfalfa Cultivars and Genotypes (Medicago sativa L) - SENGUL , SULEYMAN; HALILOGLU, K. (Asian Journal of Chemistry, 2010)
Increasing forage yields remains a top of most alfalfa (Medicago sativa) breeding programs besides yield other agronomic traits need to be considered in additive to yield, especially when trying to develop breeding material from non adapted materials. Four cultivars and seventeen genotypes were examined in a field experiment in 2003-2004. Crude protein (CP), dry matter (DM), P, K, Mg, Na, Ca, Fe, Cu, Mn and Zn as a mineral concentration, neutral detergent fiber (NDF), acid detergent lignin (ADL) and acid detergent fiber (ADF) as a cell-wall energy content were studied. A greater proportion of significant phenotypic variations were observed among genotypes. Considerable significant correlations in chemical concentrations between genotypes were measured. Amongst the characteristics examined in this experiment there are highly negative significant correlation observed between DM with P (r = -0.479**), Zn (r = -0.419**), NDF (r = -0.971**), ADL (r = -0.792**) and ADF (r = -0.819**). Highly significant positive relationships were determined between NDF and P (r = 0.416**), Zn (r = 0.415**). ADL measurement revealed significant correlation with P (r = 0.309*), Cu (r = 0.438**) and NDF (r = 0.754**). There are highly positive significant correlation observed between ADF with NDF (r = 0.814**) and ADL (r = 0.815**). This result suggest that Savas cultivar, Gülsinberk, Mahmudiye and Adigüzel genotypes should provide useful genetic material for enhancing mineral concentration in alfalfa forage. The variation could be exploited as an additional source of genetic variation in breeding programs for quality trials to achieve a higher genetic gain for breeding cycle.